Nutritional stress targets LeishIF4E-3 to storage granules that contain RNA and ribosome components in Leishmania. - Rohit Shrivastava; Matan Drory-Retwitzer; Michal Shapira (Public Library of Science (PLoS), 2019)
Leishmania parasites lack pathways for de novo purine biosynthesis. The depletion of purines induces differentiation into virulent metacyclic forms. In vitro, the parasites can survive prolonged periods of purine withdrawal changing their morphology to long and slender cells with an extended flagellum, and decreasing their translation rates. Reduced translation leads to the appearance of discrete granules that contain LeishIF4E-3, one of the six eIF4E paralogs encoded by the Leishmania genome. We hypothesize that each is responsible for a different function during the life cycle. LeishIF4E-3 is a weak cap-binding protein paralog, but its involvement in translation under normal conditions cannot be excluded. However, in response to nutritional stress, LeishIF4E-3 concentrates in specific cytoplasmic granules. LeishIF4E-3 granulation can be induced by the independent elimination of purines, amino acids and glucose. As these granules contain mature mRNAs, we propose that these bodies store inactive transcripts until recovery from stress occurs. In attempt to examine the content of the nutritional stress-induced granules, they were concentrated over sucrose gradients and further pulled-down by targeting in vivo tagged LeishIF4E-3. Proteomic analysis highlighted granule enrichment with multiple ribosomal proteins, suggesting that ribosome particles are abundant in these foci, as expected in case of translation inhibition. RNA-binding proteins, RNA helicases and metabolic enzymes were also enriched in the granules, whereas no degradation enzymes or P-body markers were detected. The starvation-induced LeishIF4E-3-containing granules, therefore, appear to store stalled ribosomes and ribosomal subunits, along with their associated mRNAs. Following nutritional stress, LeishIF4E-3 becomes phosphorylated at position S75, located in its less-conserved N-terminal extension. The ability of the S75A mutant to form granules was reduced, indicating that cellular signaling regulates LeishIF4E-3 function.